2017
DOI: 10.1097/md.0000000000007605
|View full text |Cite
|
Sign up to set email alerts
|

Continuous use of metformin can improve survival in type 2 diabetic patients with ovarian cancer

Abstract: Evidence indicates that type 2 diabetes may stimulate the initiation and progression of several types of cancer. Metformin, a drug most commonly used to treat type 2 diabetes, may inhibit cancer cell growth and reduce the risk of cancer. However, evidence of the antitumor effects of metformin on ovarian cancer is still limited.In this study, we retrospectively examined the effects of metformin on ovarian cancer patients with diabetes at our institution.We identified 568 consecutive patients who were newly diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
2
37
0
1
Order By: Relevance
“…The results of some previous studies have suggested that metformin use is associated with better survival in cases of ovarian cancer [ 6 8 , 37 ] unlike in our study, whereas similarly to our findings, in one study such an association was not found [ 38 ]. The most recent study on metformin and OC survival also suggested that continuous use of metformin in women with T2D decreases the occurrence of relapses of ovarian cancer and ovarian cancer-related deaths [ 37 ]. In line with our findings, Garcia et al found no association between metformin use and better overall survival [ 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…The results of some previous studies have suggested that metformin use is associated with better survival in cases of ovarian cancer [ 6 8 , 37 ] unlike in our study, whereas similarly to our findings, in one study such an association was not found [ 38 ]. The most recent study on metformin and OC survival also suggested that continuous use of metformin in women with T2D decreases the occurrence of relapses of ovarian cancer and ovarian cancer-related deaths [ 37 ]. In line with our findings, Garcia et al found no association between metformin use and better overall survival [ 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…incidence and survival, it was proposed that metformin should be followed as an additional approach in ovarian cancer treatment. [63][64][65] As metformin treatment is associated with an increased PR expression, these results further support future investigations of the above-described relationships in the NRF2/AKR1C1/PR pathway and their impact on ovarian cancer biology and the clinical behavior.…”
Section: Discussionsupporting
confidence: 77%
“…Many studies have shown that metformin can reduce the risk of cancer, including breast, colon, liver, and pancreatic cancers, and improve outcomes over those obtained with other antidiabetic treatments (sulfonylurea, insulin) in diabetic patients [9]. Whether metformin can reduce the risk of ovarian cancer has been investigated [22][23][24], but few studies have focused on the effects of metformin combined with commonly used rst-line chemotherapeutic drugs, such as carboplatin, and the underlying mechanisms [25]. Neoadjuvant metformin combined with other therapies have been administered to treat ER-positive breast cancer in a Phase II clinical trial (ClinicalTrials.gov Identi er: NCT01589367).…”
Section: Discussionmentioning
confidence: 99%